STAG1 mutations cause a novel cohesinopathy characterised by unspecific syndromic intellectual disability. Issue 7 (24th January 2017) - Lehalle, Daphné; Mosca-Boidron, Anne-Laure; Begtrup, Amber; Boute-Benejean, Odile; Charles, Perrine; Cho, Megan T; Clarkson, Amanda; Devinsky, Orrin; Duffourd, Yannis; Duplomb-Jego, Laurence; Gérard, Bénédicte; Jacquette, Aurélia; et al.
Abstract : Background: Cohesinopathies are rare neurodevelopmental disorders arising from a dysfunction in the cohesin pathway, which enables chromosome segregation and regulates gene transcription. So far, eight genes from this pathway have been reported in human disease. STAG1 belongs to the STAG subunit of the core cohesin complex, along with five other subunits. This work aimed to identify the phenotype ascribed to STAG1 mutations. Methods: Among patients referred for intellectual disability (ID) in genetics departments worldwide, array-comparative genomic hybridisation (CGH), gene panel, whole-exome sequencing or whole-genome sequencing were performed following the local diagnostic standards. Results: A mutation in STAG1 was identified in 17 individuals from 16 families, 9 males and 8 females aged 2–33 years. Four individuals harboured a small microdeletion encompassing STAG1 ; three individuals from two families had an intragenic STAG1 deletion. Six deletions were identified by array-CGH, one by whole-exome sequencing. Whole-exome sequencing found de novo heterozygous missense or frameshift STAG1 variants in eight patients, a panel of genes involved in ID identified a missense and a frameshift variant in two individuals. The 17 patients shared common facial features, with wide mouth and deep-set eyes. Four individuals had mild microcephaly, seven had epilepsy. Conclusions: We report an international series of 17 individuals from 16 families presenting with syndromic unspecific ID that could be attributed to a STAG1 deletion or point mutation. This first series reporting the phenotype ascribed to mutation in STAG1 highlights the importance of data sharing in the field of rare disorders.